МORPHOLOGICAL RESULT OF DENTAL IMPLANTATION IN PATIENTS WITH DIABETES MELLITUS - Achilova Nodira Ganievna (TADQIQOTLAR, 2026)
Abstract Dental implantation is increasingly performed in older populations, who frequently present with systemic comorbidities such as diabetes mellitus. The present study aimed to identify morphological predictors associated with postoperative complications and implant success in this high-risk cohort. A total of 30 patients aged 40–65 years were examined, including individuals with varying severity of periodontal disease. Histological and immunohistochemical analyses of gingival tissues were conducted to assess local immune responses. The findings demonstrate that alterations in mucosal immune homeostasis—particularly increased mast cell density, macrophage infiltration, and antigen-presenting cell activity—are strongly associated with postoperative complications. Patients with diabetes exhibited significantly higher rates of inflammatory responses and delayed healing. Morphological changes in trabecular bone structure correlated with disease severity and implant prognosis. These results suggest that immunocompetent cells within the oral mucosa may serve as reliable biomarkers for predicting implant outcomes. Preoperative immunomodulatory strategies and careful patient selection are critical to improving clinical success rates.